Black and white or shades of grey: Religious approaches and Muslim marital conflict. (March 2022) - Shah, Sarah
While the diversity of diasporic Muslim public experiences has been examined, the social contours of religious approach have received less attention. Moreover, the ways in which religion shapes marital relations remains understudied. This article, which features data from a larger research project, highlights two divergent trends in Muslim approaches to religion: exclusivity, which frames only one approach to Islam as correct, and inclusivity, which frames multiple approaches as correct. This divergence plays a role in shaping definitions of 'good Muslim', as exclusivist Muslims focus on ritual acts (outward observance), while inclusivist Muslims prioritize good manners (inward observance). The author demonstrates how these inward and outward definitions of Muslimness in turn inform how participants evaluate their spouses' religiosity and, thus, the potential for conflict over religiosity with their spouses.